King's mountain : a ballad novel - McCrumb, Sharyn, 1948- (McCrumb, Sharyn, 1948- Ballad novels., 2013)
"From the New York Times bestselling author--the first Ballad novel to feature the epic, and gorgeously-portrayed, American Revolution. John Sevier had not taken much interest in the American Revolution, he was too busy fighting Indians in the Carolinas and taming the wilderness. But when an arrogant British officer threatened his settlement--promising to burn the farms and kill families--the war became personal. That arrogant officer is Patrick Ferguson of the British Army--who is both charmingly antagonistic and surprisingly endearing. Inventor of the Ferguson rifle, and the devoted lover to his mistress, Virginia Sal, Patrick becomes a delightful anti-hero under McCrumb's watchful eye. Through varying perspectives, King's Mountain is an elegant saga of the Carolina Overmountain Men--the militia organized by Sevier (who would later become the first governor of Tennessee) and their victory in 1780 against the Tories in a battle that Thomas Jefferson later called, "The turning point of the American Revolution." Peppered with lore and the authentic heart of the people in McCrumb's classic Ballads, this is an epic book that will build on the success of The Ballad of Tom Dooley and her recent return to the New York Times bestseller list. Featuring the American Revolution, this a huge draw to readers old and new, and special to McCrumb who can trace her lineage to the character John Sevier"--